PERAN AUDIT SYARIAH DALAM PELAYANAN PERBANKAN SYARIAH UNTUK MENINGKATKAN KEPERCAYAAN MASYARAKAT - Mafikah, Ananta Delyana; Latifah, Eny (JITAA : Journal Of International Taxation, Accounting And Auditing, 2022)
This research investigates the important role of sharia audit in increasing public trust in sharia banking services. The title was chosen to view the important contribution of sharia audit as a mechanism for monitoring and ensuring compliance with sharia principles in bank operations. The aim of the research is to evaluate the extent to which sharia audits can strengthen the integrity and transparency of sharia financial institutions. The research method involves document analysis, so that there are results to gain in-depth insight. The research results show that sharia audits have a positive impact in creating a more trustworthy sharia banking environment, ensuring compliance with Islamic ethical values, and strengthening harmonious relations between sharia banks and their communities.